The effects of trust on consumers’ continuous purchase intentions in C2C social commerce: A trust transfer perspective - Zhao, Jing-Di; Huang, Jin-Song; Su, Song (Journal of retailing and consumer services, 2019)
This study develops a trust mechanism based on trust transfer theory in the context of customer-to-customer (C2C) social commerce. Based on combined data from 206 sellers and consumers, this study finds that customers have continuous purchase intentions when they trust sellers and brands at the same time and that consumers generate brand trust due to trust in sellers. In addition, with informational and emotional support, consumers can generate trust in individual sellers. Finally, promotion, which is a common strategy used by C2C sellers, will damage the trust transfer from sellers to the brand.